Malnutrition among Children: Some reviews from India, developing and underdeveloped Countries: – - Pawar, Pratima (Advances in Social Sciences Research Journal, 2021)
Abstract: Nutrition has major effects on health. Malnutrition refers to any imbalance in satisfying nutrition requirements. Malnutrition is often cited as an important factor contributing to high morbidity and mortality among children in developing countries. Malnourished children are more likely to grow into malnourished adults who face increased risks of disease and death. A number of factors affect child nutrition, either directly or indirectly. The most commonly cited factors are food availability and dietary intake, breastfeeding, prevalence of infectious and parasitic diseases, vitamin A supplementation, maternal care during pregnancy, water supply and sanitation, socio-economic status, and health-seeking behavior. Thus malnutrition is a serious problem which directly or indirectly affects the social and economic development of a nation. The present paper focuses on the scenario of malnutrition based on the reviews in different developing countries including India.